2018
DOI: 10.1002/cam4.1884
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐institutional retrospective study of carbon‐ion radiotherapy for non‐squamous cell malignant tumors of the nasopharynx: Subanalysis of Japan Carbon‐Ion Radiation Oncology Study Group study 1402 HN

Abstract: BackgroundThis multi‐institutional retrospective study focused on the clinical outcome of carbon‐ion radiotherapy (C‐ion RT) for non‐squamous cell malignant tumors of the nasopharynx.MethodsThe Japan Carbon‐ion Radiation Oncology Study Group collected and analyzed data for 43 patients with non‐squamous cell malignant tumors of the nasopharynx treated with C‐ion RT at four institutions in Japan.ResultsTwenty‐nine patients had adenoid cystic carcinomas, seven had malignant melanomas, three had adenocarcinomas, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The results indicated the safety of the combined treatment, and patients with macroscopically complete resection and gross residual tumors had similar toxicities. Ten articles (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were published from PBRT centers in Japan based on their registered studies, and most were retrospective. The studies were registered on UMIN-CTR shortly before the publication of the papers (date of registration in relation to publication not shown in our analysis).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated the safety of the combined treatment, and patients with macroscopically complete resection and gross residual tumors had similar toxicities. Ten articles (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) were published from PBRT centers in Japan based on their registered studies, and most were retrospective. The studies were registered on UMIN-CTR shortly before the publication of the papers (date of registration in relation to publication not shown in our analysis).…”
Section: Discussionmentioning
confidence: 99%
“…The grade 3 or higher toxicity rate was 15%, with 2 patients experiencing a grade-5 pharyngeal hemorrhage [ 33 ]. In 2018, Abe et al [ 34 ] followed with a subgroup analysis of nasopharyngeal disease, including 29 ACCs and 7 MMs treated with 64 GyRBE; 2-year LC was 88%, with 1 grade-4 optic nerve and 2 grade-5 pharyngeal hemorrhages. Ikawa et al [ 35 ] conducted a histologic analysis for solid growth pattern H&NACC, finding no difference in LC between subtypes, though there were differences in OS and PFS.…”
Section: Adenoid Cystic Carcinomamentioning
confidence: 99%
“…The pioneering investigations at LBNL showed that fractionated delivery of heavy ion therapy, generally as a boost at relatively low doses, was well tolerated across diverse tumor sites, including locally advanced prostate cancer, bone and soft tissue sarcomas, and head and neck tumors of the salivary gland and paranasal sinus . Subsequent phase I/II trials conducted largely in Japan and Germany employing higher doses and conducted primarily solely with CIRT have demonstrated negligible toxicity and encouraging tumor control rates in diverse histologic tumor types, including adenocarcinoma, adenoid cystic carcinoma, malignant melanoma, and bone and soft tissue sarcomas, tumors which are often resistant to conventional photon irradiation . Additional difficult to treat tumor sites with early favorable outcomes include tumors of the lung, liver, and pancreas.…”
Section: Opening Statementsmentioning
confidence: 99%